Interexaminer reliability of thoracic motion palpation using confidence ratings and continuous analysis - Cooperstein, Robert; Haneline, Michael; Young, Morgan (Journal of chiropractic medicine, 2010)
Motion palpation is integral to most chiropractic techniques and can be found in curricula of most every chiropractic college. Paradoxically, most studies do not show strong reliability for motion palpation. The purpose of this study was to determine if allowing motion palpators to rate their confidence in their findings, as well using a continuous data analytic method, would influence the level of concordance. Subjects were 52 asymptomatic chiropractic student volunteers. Two palpators assessed posterior to anterior glide of T3-10 in the prone position, alternating in their order and blinded as to each other's results. Each examiner identified the location of maximal restriction in this range and also whether they were “very confident” or “not confident” in their finding. For all subjects combined, the examiners' calls were “poor”: intraclass correlation coefficient [2,1] = .3110 (95% CI, .0458-.5358). In contrast, interexaminer agreement was “good” when both examiners were very confident: intraclass correlation coefficient [2,1] = .8266 (95% CI, 0.6257-0.9253). When each examiner was “very confident” as to the most fixated thoracic segment, the levels they identified were very close. This corresponds to “good” agreement, an uncommon result in most interexaminer motion palpation studies. Thus, the confidence level of examiners had an effect on the interexaminer reliability of thoracic spine. Our novel continuous measures, statistical methodology, and subtyping the subjects according to the confidence of the palpators seem more capable than level-by-level discrete analysis of detecting interexaminer agreement.